(untitled) (Research, Society and Development, 2022)
In the Maranhão’s state there is an extensive area of water resources, with ten basins and two hydrographic systems, however there is a significant shortage of studies related to water potability standards in small cities requiring more research focused on the type of supply and monitoring the quality of the water used by the population of the cities of Maranhão. Thus, in this work, the type of supply and monitoring of the quality of water for human consumption in the Coelho Neto’s city Maranhão, was identified, seeking to quantify the wells, verifying the procedures for collecting, packaging, transporting and analyzing samples during monitoring quality of water for human consumption, checking the quality of the water from the wells that supply the Coelho Neto’s city Maranhão, also evaluating the population’s understanding of the quality of water consumed in the municipality.The study was carried out through bibliographical research and field research carried out in the main neighborhoods of the city with wells in operation, the Annual Water Quality Reports of the Environmental Sanitation Company of Maranhão - CAEMA from 2016 were used as data query, 2017 and 2018, as well as quantification data from the wells of the Mineral Resources Research Company-CPRM and the Autonomous Water and Sewage System-SAAE and Municipal Health Department of the municipality and the use of a questionnaire with the intention of evaluating the understanding of the population on issues related to the quality of water consumed/distributed. The analyzes could be carried out in the field, but the lack of structure and instruments makes it unfeasible, it found the lack of data on the registration of the number of private wells, which makes it difficult to monitor and collect accurate data. There is a need for investment in the Basic Sanitation sector in urgency character in the municipality as well as improvement in the conditions of monitoring the quality of drinking water and a commitment of the population in decision-making in water management in the Coelho Neto’s city Maranhão.